SEASONAL VARIATIONS OF TISSUE CALCIUM AND PHOSPHORUS IN THE JUVENILES OF THE CATFISH, WALLAGO ATTU (BL. & SCHN.). - Jafri, A K; Khawaja, D K (Indian Journal of Fisheries, 2011)
Seasonal variations have been studied in calcium and phosphorus contentsof muscle and liver of juveniles of the cat-fish, Walldgo attu (Bl. & Schn.)- Thevariations in the quantity of these minerals in the two tissues followed well-defln'3dcycles and these were identical in the juveniles of the two size-groups investigated.The rise and fall in the calcium and phosphorus values have been attributed mainlyto the f'seding rhythm of these sexually immature fishes.